English Communicative Events and Skills Needed at the Workplace: Feedback From the Industry - Hafizoah, Kassim; Fatimah, Ali (Elsevier Ltd., 2010)
The constant and continuous need for the university to work towards producing graduates who meet and exceed the requirements of their chosen industry has prompted the effort to gather feedback from those industries. The effort by researchers of an engineering-based university in the East Coast Region of Malaysia to collect information on the important communication skills and communicative events frequently faced and utilized by engineers has assisted in the design of an English communication syllabus and module for engineering students. Self-developed questionnaires were administered to engineers of 10 multinational chemical companies all around Malaysia. The results depict that emphasis should be put on oral, rather than written, communication skills. Moreover, findings also indicate that the communicative events considered important for engineers are: teleconferencing, networking for contacts and advice, and presenting new ideas and alternative strategies. Fluency in the English language is seen as an opportunity in the engineering field to advance towards becoming a global engineer. The pedagogical implications of the findings indicate that module design and development should take into consideration the incorporation of workplace scenarios as the basis for activities.